Desertification in the Mediterranean Region. A Security Issue - Kepner, William G.; Rubio, Jose L.; Mouat, David A.; Pedrazzini, Fausto; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book focuses on two basic concepts: security and desertification in the Mediterranean Region and their linkages. It emerged from a single meeting of the "Workshop on Desertification in the Mediterranean Region. A Security Issue" held in Valencia, Spain on 2-5 December 2003, which was sponsored by the NATO Science Committee and NATO Committee on the Challenges of Modern Society. Desertification is recognized as a process of land degradation in arid, semi-arid, and dry sub-humid areas of the world that is the result of natural phenomena (e.g. climate variation) and anthropogenic factors. The outcome of this type of degradation has typically been considered to be either a reduction or a loss of both biological and economic productivity. The scope of the book includes the identification of the physical processes of desertification specific to both the north and south Mediterranean Region. Additionally, it specifically questions how changing environmental conditions may potentially reduce stability and peace in the world and thus affect "environmental security." During the workshop an array of government diplomats, security specialists, and social and physical scientists from the Middle East, North Africa, Europe, and North America reviewed the actions of past and current Mediterranean land use practices, especially in regard to environmental security, environmental consequences, and challenges for the future. The book is divided into six special topical areas dealing with Linking Environmental Condition to Security; Assessing Regional Conditions; Assessing Land Use Change Relative to Human-induced and Natural Cause; Opportunities for Regional Cooperation and Information Sharing; Soil and Vegetation Monitoring; and Development of Regional Desertification Indicators and Forecasting Techniques. This book provides a multi-lateral forum for cooperation, information exchange, and dialogue among the environmental, development, foreign and security policy communities within the Mediterranean Region and thus may provide a precedent for further cooperation and partnership, including other more advanced conferences and publications, on assessing the condition of the entire region and the subsequent impacts and linkages to environmental security.
Introduction: Desertification in the Mediterranean Region: Linking Environmental Condition to Security. -- INTRODUCTION: DESERTIFICATION AND SECURITY Perspectives for the Mediterranean Region -- DESERTIFICATION - A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global environmental change and potentially violent societal consequences -- THE POSEIDON PRAIRIE Desertification, Environmental Stress, and the Euro-Mediterranean Space -- DESERTIFICATION AND ENVIRONMENTAL SECURITY. THE CASE OF CONFLICTS BETWEEN FARMERS AND HERDERS IN THE ARID ENVIRONMENTS OF THE SAHEL -- THE RELEVANCE AND CONSEQUENCES OF MEDITERRANEAN DESERTIFICATION INCLUDING SECURITY ASPECTS -- Mediterranean Regional Perspective on Assessment and Condition -- PROBLEMATIQUE DE LA DESERTIFICATION EN ALGERIE: ETAT ET MESURES DE LUTTE POUR LA PROTECTION DES RESSOURCES NATURELLES -- SECURITY IMPACTS OF DESERTIFICATION IN EGYPT -- THE CHALLENGES OF LAND AND WATER RESOURCES DEGRADATION IN JORDAN: DIAGNOSIS AND SOLUTIONS -- DRYLAND DEVELOPMENT, DESERTIFICATION AND SECURITY IN THE MEDITERRANEAN -- STATE OF NATURAL RESOURCES DEGRADATION IN MOROCCO AND PLAN OF ACTION FOR DESERTIFICATION AND DROUGHT CONTROL -- DESERTIFICATION, TERRITORY AND PEOPLE, A HOLISTIC APPROACH IN THE PORTUGUESE CONTEXT -- MIGRATION: AN IRREVERSIBLE IMPACT OF LAND DEGRADATION IN TURKEY -- Assessing Land Use Change Relative to Anthropogenic and Natural Cause -- DOES ANTHROPOGENIC ACTIVITIES OR NATURE DOMINATE THE SHAPING OF THE LANDSCAPE IN THE OREGON PILOT STUDY AREA FOR 1990-1999? -- URBAN GROWTH DYNAMICS (1956-1998) IN MEDITERRANEAN COASTAL REGIONS: THE CASE OF ALICANTE, SPAIN -- LAND USE CHANGE DETECTION AS A BASIS FOR ANALYSING DESERTIFICATION PROCESSES: A CASE STUDY IN TABERNAS (ALMERIA, SPAIN) -- CLIMATE CHANGE, LAND DEGRADATION, AND DESERTIFICATION IN THE MEDITERRANEAN ENVIRONMENT -- Regional Cooperation and Information Sharing -- THE ENVIRONMENT AND SECURITY INITIATIVE: TRANSFORMING RISKS INTO OPPORTUNITIES FOR CO-OPERATION -- Fostering networking and exchange of information in the Mediterranean region: The MEDCOASTLAND Thematic Network1 -- DESERTIFICATION IN THE ARID AND SEMIARID MEDITERRANEAN REGIONS. A FOOD SECURITY ISSUE -- Soil and Vegetation Monitoring -- MONITORING TOOLS TO ASSESS VEGETATION SUCCESSIONAL REGRESSION AND PREDICT CATASTROPHIC SHIFTS AND DESERTIFICATION IN MEDITERRANEAN RANGELAND ECOSYSTEMS -- USING A GIS FOR SUSTAINABLE USE AND MANAGEMENT OF AN IRRIGATION AREA IN THE SPANISH - PORTUGUESE BORDER THREATENED BY DESERTIFICATION -- RESTORATION OF BURNED AREAS IN FOREST MANAGEMENT PLANS -- IMPACT OF FOREST FIRES ON HYDROLOGICAL PROPERTIES OF A TYPICAL MEDITERRANEAN FOREST SOIL -- MANAGEMENT OF FOREST SOILS CONSIDERING WATER EROSION AS A CONTROL FACTOR -- Desertification Indicators and Forecasting Techniques -- ENVIRONMENTALLY SENSITIVE AREAS AND INDICATORS OF DESERTIFICATION -- DESERTIFICATION IN NORTHERN MOROCCO DUE TO EFFECTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE -- HYDROLOGICAL APPROACH FOR ASSESSING DESERTIFICATION PROCESSES IN THE MEDITERRANEAN REGION -- THE USE OF ALTERNATIVE FUTURES IN A STRATEGY TO ASSESS THE LIKELIHOOD OF LAND DEGRADATION LEADING TO INCREASED SUBSEQUENT POLITICAL INSTABILITY.
Keywords: ENVIRONMENTAL SCIENCES; LANDSCAPE ECOLOGY; SOCIAL SCIENCES; HUMAN GEOGRAPHY; ENVIRONMENT; ENVIRONMENT, GENERAL; LANDSCAPE ECOLOGY; REGIONAL SCIENCE; HUMAN GEOGRAPHY; SOCIAL SCIENCES, GENERAL